“Knowing Me, Knowing You” the Importance of Networking for Freelancers’ Careers: Examining the Mediating Role of Need for Relatedness Fulfillment and Employability-Enhancing Competencies - Jacobs, Sofie; De Vos, Ans; Stuer, David; Van der Heijden, Beatrice I. J. M. (Frontiers in Psychology, 2019)
Research has shown the importance of engaging in networking behaviors for employees’ career success. Networking behaviors can be seen as a proactive way of creating access to career-related social resources and we argue that this type of proactive career behaviors might be particularly relevant for freelancers who cannot depend on an organizational career system supporting their further development, yet whose careers are characterized by high levels of uncertainty and unpredictability. To date, however, our understanding of how freelancers, being a category of workers that are deprived of an organizational context of support for career development, can safeguard their employability, is limited. Therefore, this study addresses this gap and investigates whether freelancers’ networking behaviors are positively associated with career outcomes, through the mediating role of the need for relatedness fulfillment and employability-enhancing competencies. Hypotheses are tested via Structural Equation Modelling using a sample of 1,874 freelancers from Belgium, France, Germany, the Netherlands and the United Kingdom. The results generally support our hypotheses, providing evidence for a significant association between networking behaviors and need for relatedness fulfillment, and between networking behaviors and employability-enhancing competencies. Moreover, we found a significant association between need for relatedness fulfillment and employability-enhancing competencies, being the mediators in our research model and the outcomes of career satisfaction and future career opportunities. Implications for career development in the contemporary workplace are discussed, with particular attention for need for relatedness fulfillment, employability, and sustainable careers of freelance workers.